Social Capital and Social Innovation in Peripheral Regions. An Empirical Example of the Middle Pomerania Region in Poland - Malgorzata CZERWINSKA-JASKIEWICZ (Communications of International Proceedings, 2025)
In this article, the author attempts to assess selected components of social capital in the context of stimulating social innovation in peripheral areas. The Middle Pomerania region serves as an empirical example. It is the region that is specific in terms of history and structure, which, despite the lack of formal delimitation in the administrative division, exhibits relative economic and social cohesion, while at the same time displaying high intra-regional diversity. The main objective of the article is to diagnose and assess the innovation potential of local communities operating within social organisations, which are main players in the creation of a regional innovation system. The results of the empirical research indicate that the peripherality of the region, although considered rather a dissimulating feature, can in itself be a catalyst for local activity. The inhabitants declare that the Middle Pomerania region, although peripheral, has sufficient social capital resources to create changes and social innovation. In her conclusions, the author suggests constant monitoring of the social capital in peripheral regions and encourages the building of relationships in the region through, among other things, supporting the activities of social organisations. These organisations can and should become stimulators of development for marginalised regions.
Keywords: social capital; social innovation; peripheral region; The Middle Pomerania region.